Analisis Kinerja Jaringan Internet di Lingkungan Akademik dengan Pendekatan Quality of Service (QoS): Studi Kasus di Universitas Pamulang - Jiyan Suhada; Hari Setyawan; Kelvin Andrean (PT Pustaka Cendekia Group, 2025)
The availability of reliable and high-quality internet networks is critical in supporting the learning process in higher education institutions. This study aims to analyze the quality of the internet network at Universitas Pamulang using the Quality of Service (QoS) method to improve learning performance. The research was conducted by measuring QoS parameters, including throughput, delay, packet loss, and jitter at various network points within the campus area. Data collection methods were carried out using network measurement tools and simulations of various network load scenarios. The research results show that the internet network performance at Universitas Pamulang varies significantly in quality across different locations. The measurement results indicate an average throughput of 4.94 bps, an average delay of 0 ms, an average jitter of 0, and an average packet loss of 11.46, based on TIPHON standards. Overall, the QoS index of the internet network at Universitas Pamulang is 2.75. Recommendations for improvements include increasing bandwidth capacity, optimizing network configuration, and implementing more efficient traffic management